Emergency contraception amongst medical college students: knowledge, attitude, practice - Patni, MohamedAnas M.; Gamit, Sukesha; Damor, Rahul (International Journal Of Community Medicine And Public Health, 2018)
Background: Emergency contraception has the potential to greatly reduce the number of unintended pregnancies. The level of knowledge among the medical student population about EC has not been adequately investigated. This study aims to assess the knowledge, attitude and practice of EC (Emergency Contraception) amongst the medical under graduate students in Government college of Surat. Methods: This study was carried out among 339 medical under graduate students during the month of October, 2016. A predesigned self-administered questionnaire was used to collect the data. Results: Majority of students knew about some form of contraception. Only quarter of students knew about EC pill. Varied responses were observed regarding various knowledge aspects of EC. Internet and books were the most common source of knowledge. As far as their attitudes are concerned, almost 40% believed that EC would lead more irresponsible behaviour and more STD/HIV cases, while 30% believed that it would lead to promiscuity, and be inexpensive, if they are readily available. More than half number of students opined that EC should be made available for women aged only 18 years and above. As far as practice is concerned, only one student reported using EC. However, more than 40% were willing to use it, if required and would also encourage friends and relatives to use it. Conclusions: Awareness of EC was low among students. Attitude was favorable towards EC. Study also document very low level of practice of EC among the students.